2022
DOI: 10.35869/reined.v20i1.3964
|View full text |Cite
|
Sign up to set email alerts
|

Narrativas del alumnado de Educación Primaria sobre su bienestar escolar: un diagnóstico inicial

Abstract: El interés por conocer el bienestar dentro de los centros educativos, sobre todo, desde la perspectiva de sus protagonistas, los niños y las niñas, ocupa un lugar central en la investigación actual. El objetivo de la investigación fue indagar acerca de los indicadores que configuran el bienestar escolar del alumnado de Educación Primaria. Se realizó un estudio cualitativo, en el que participaron 95 estudiantes de dos centros educativos públicos, a los que se les aplicó el Cuestionario Abierto de Bienestar Esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, the use of AR in academia suggests offering extraordinary experiences to students, by facilitating a friendlier environment and increasing attention (Adedokun-Shittu et al, 2020). Thus, students' attitude towards AR-based applications has been mostly evaluated in longitudinal design studies, where students indicated to be very happy by the use of this innovative learning methodology (McBain et al, 2022), which starts from the students' prior knowledge to favor the personalization of teaching (Soriano-Sánchez & Jiménez-Vázquez, 2023), guaranteeing the students' well-being (Requejo et al, 2022) and increasing their academic performance (Soriano-Sánchez & Jiménez-Vázquez, 2022a).…”
Section: Advantages Of Augmented Reality In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of AR in academia suggests offering extraordinary experiences to students, by facilitating a friendlier environment and increasing attention (Adedokun-Shittu et al, 2020). Thus, students' attitude towards AR-based applications has been mostly evaluated in longitudinal design studies, where students indicated to be very happy by the use of this innovative learning methodology (McBain et al, 2022), which starts from the students' prior knowledge to favor the personalization of teaching (Soriano-Sánchez & Jiménez-Vázquez, 2023), guaranteeing the students' well-being (Requejo et al, 2022) and increasing their academic performance (Soriano-Sánchez & Jiménez-Vázquez, 2022a).…”
Section: Advantages Of Augmented Reality In Higher Educationmentioning
confidence: 99%
“…Throughout history, human beings have been able to evolve and adapt to different situations thanks to their ways of communicating . Currently, in the 21st century society, education requires a coherent training that allows a response to the presence of information and communication technologies (ICT) through active and dynamic approaches (Day et al, 2021), which promote the well-being of students (Requejo et al, 2022). This requires a methodological change that allows the adaptation of material resources to the required competencies (Sáez-López et al, 2020).…”
Section: Introductionmentioning
confidence: 99%